Urgensi Tafsir Kontekstual dalam Penafsiran Al-Qur’an - Mustaqimah Mustaqimah (Farabi, 2015)
The backwardness of Muslims civilization today support to reflection in an attempt to find a way towards a revival. One was taken to the efforts is reinterpretation of Islamic texts (Koran) in accordance with the spirit of this time. Efforts are being made to the hermeneutic method is commonly called contextualization, complement some of the approaches that have been there before. In this paper the authors conclude that the tradition of critical thinking, creative and innovative to do with getting rid of prejudice and negative assumptions, and rationality. Therefore, efforts to understand the Qur'an with various new methodological approaches should be developed and should not stop at one point.